2020
DOI: 10.1186/s12891-020-03657-9
|View full text |Cite
|
Sign up to set email alerts
|

A real 3D measurement technique for the tibial slope: differentiation between different articular surfaces and comparison to radiographic slope measurement

Abstract: Background The tibial slope plays an important role in knee surgery. However, standard radiographic measurement techniques have a low reproducibility and do not allow differentiation between medial and lateral articular surfaces. Despite availability of three-dimensional imaging, so far, no real 3D measurement technique was introduced and compared to radiographic measurement, which were the purposes of this study. Methods Computed tomography scans of 54 knees in 51 patients (41 males and 10 females) with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The measurement of the TS in lateral radiography is limited. Especially, differences between the medial and lateral knee-joint compartment are not exactly assessable a priori [ 5 , 27 , 40 ]. Our study demonstrated a significantly higher TS on the lateral articular surface, independent of the measurement method that was used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The measurement of the TS in lateral radiography is limited. Especially, differences between the medial and lateral knee-joint compartment are not exactly assessable a priori [ 5 , 27 , 40 ]. Our study demonstrated a significantly higher TS on the lateral articular surface, independent of the measurement method that was used.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature indicates a highly variable intra-individual TS [ 7 , 22 , 26 ]. However, the reference values are based on different imaging procedures and measurement methods [ 5 , 26 , 27 ]. The measurement of the TS in the lateral radiographs of the knee has been described to be limited, because the determination can only be performed on the basis of a single radiological projection [ 5 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The greatest advantage of a 3D CT scan over radiography is elimination of errors due to the rotational profile of the tibia and accurate analysis by referencing the anatomic axis. 34 Moreover, it allows independent assessment of both medial and lateral plateaus and the peripheral rim with a high degree of reliability and accuracy 35 (Figure 4). The centers of circles touching the anterior and posterior tibial cortices at 5 cm.…”
Section: Three-dimensional Ct Scanmentioning
confidence: 99%